Optimization of heat treatment program and effect of heat treatment on microstructure and flexural strength of micro-nano-Li2Si2O5 whisker-reinforced glass-ceramics - He, Wenli; Yao, Chengliang; Zhao, Zihan; Rong, Cunren; Zhang, Yanjie; Li, Bing; Wu, Xiuping (Frontiers in Materials, 2023)
Lithium disilicate （Li2Si2O5， referred as LD） glass ceramics with unique aesthetic properties are ideal dental restorative materials, however, their applications are limit due to the lower flexural strength than polycrystalline ceramics. Herein, micro-nano-LD whiskers were utilized to facilitate the formation of crystallization sites and further growth of crystals in SiO2-Li2O glasses during the heat treatment process. Meanwhile, an orthogonal experiment with four-factor three-level was designed, and the optimum heat treatment conditions for preparing LD glass-ceramics with excellent flexural strength were found. The order of influencing extent of heat treatment conditions is crystallization temperature > crystallization time > nucleation temperature > nucleation time. In addition, the crystallization behavior, phase formation, microstructure and flexural strength of glass were measured at different heat treatment temperatures. Remarkably, the optimal LD glass-ceramics sample has a strong flexural strength at 342 MPa, in which plentiful crystal grains with uniform and dense distribution are observed. These results indicate that micro-nano-LD whisker-reinforced glass-ceramics obtained by optimized heat treatment program offer a potential candidate for dental applications.